2021
DOI: 10.4049/jimmunol.2000447
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Responses of Thitarodes xiaojinensis β-1,3-Glucan Recognition Protein-1 and Immulectin-8 to Ophiocordyceps sinensis and Cordyceps militaris Infection

Abstract: Melanization and encapsulation are prominent defense responses against microbes detected by pattern recognition receptors of their host insects. In the ghost moth Thitarodes xiaojinensis, an activated immune system can melanize and encapsulate the fungus Cordyceps militaris. However, these responses were hardly detected in the host hemolymph postinfection of another fungus Ophiocordyceps sinensis. The immune interaction between O. sinensis and the host remains largely unknown, which hinders the artificial cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…This study indicated that the upregulated genes in Tx-BP were mainly confined to PGRPs and AMPs. Our previous study showed that a protective layer existed on the cell wall of Ophiocordyceps sinensis, avoiding βGPR1 induction [ 9 ]. Consistent with this finding, changes in βGPR1 expression were not detected in the fat body of Tx-BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study indicated that the upregulated genes in Tx-BP were mainly confined to PGRPs and AMPs. Our previous study showed that a protective layer existed on the cell wall of Ophiocordyceps sinensis, avoiding βGPR1 induction [ 9 ]. Consistent with this finding, changes in βGPR1 expression were not detected in the fat body of Tx-BP.…”
Section: Discussionmentioning
confidence: 99%
“…The infection lasts at least 5 months until the host larvae are killed [ 8 ]. The unique development process of O. sinensis in ghost moth larvae and insect immunological responses during the early phase of infection (within several days) has been well described [ 7 , 8 , 9 ]. However, studies on the immune and metabolic changes of T. xiaojinensis during the long-term interaction between the host and O. sinensis are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bGRPs not only play a recognition role in Lepidopterans to trigger the innate immune response but also act in synergy with other immunity to promote antifungal defense (104). bGRP1 in T. xiaojinensis interacts with immulectin-8 (a kind of lectin) to promote encapsulation of pathogens (105). Although the role of bGRPs in viral infection needs further research, bGRPs are considered to have antiviral potential.…”
Section: Bgrp/gnbpmentioning
confidence: 99%
“…It is worth mentioning that Cordyceps has a unique way of occurring and growing in the ecosystem, and unlike normal EPF that kill their hosts in a short period, it can co-grow with its hosts for a long period for as long as half a year to a year [9]. Currently, it is hypothesized that this result is due to the defense or tolerance of the host insect immune system against O. sinensis [9][10][11][12][13]. The mechanism of host immune response to O. sinensis remains unclear, when O. sinensis freely proliferates in hemolymph.…”
Section: Introductionmentioning
confidence: 99%